2003
DOI: 10.1016/s0141-3910(02)00295-1
|View full text |Cite
|
Sign up to set email alerts
|

An XPS investigation of thermal degradation and charring on poly(vinyl chloride)–clay nanocomposites

Abstract: This paper is NOT THE PUBLISHED VERSION; but the author's final, peer-reviewed manuscript. The published version may be accessed by following the link in th citation below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 20 publications
0
42
0
Order By: Relevance
“…[1][2][3][4][5][6] Previous studies showed that PVC clay nanocomposites have intercalated or exfoliated structures depending on the type of organic modifier of the clay. 1,2,5,6 The flame retardancy, 3 dimensional stability, gas permeability barrier properties 4 , and mechanical properties 1,5,6 of PVC/clay nanocomposites could be highly enhanced with a low extent of clay addition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] Previous studies showed that PVC clay nanocomposites have intercalated or exfoliated structures depending on the type of organic modifier of the clay. 1,2,5,6 The flame retardancy, 3 dimensional stability, gas permeability barrier properties 4 , and mechanical properties 1,5,6 of PVC/clay nanocomposites could be highly enhanced with a low extent of clay addition.…”
Section: Introductionmentioning
confidence: 99%
“…However, a study on the thermal stability of PVC/clay nanocomposites by Xray photoelectron spectra reported that clay could enhance the thermal stability by delayed loss of allylic species. 3 To explore the effect of montmorillonite (MMT) on the processing discoloration and thermal degradation of PVC, we investigated the dynamic thermal degradation of PVC using thermogravimetric analysis and calculated the kinetic parameters according to the FlynnWall-Ozawa 10 and Kissinger methods. 11 In addition, the effects of sodium montmorillonite (Na ϩ -MMT) and alkyl ammonium ion modified montmorillonite (OMMT) on the processing stability and thermal degradation of PVC were also compared.…”
Section: Introductionmentioning
confidence: 99%
“…The research by Wang et al [62,[81][82][83] showed that X-ray photoelectron spectroscopy (XPS) was an effective tool to study the flame retarded mechanism of polymer/clay nanocomposites. The studies indicated that clay degrades into SiO 2 -like substances that migrate to the surface of materials during combustion.…”
Section: Flame Retarded Polymer Nanocomposites 21 Flame Retarded Polmentioning
confidence: 99%
“…These multilayered structures might be formed from the collapse of fairly dispersed clay layers during combustion. 21,29,30 But the aggregated structures of clays, which might be formed in the previous compounding step, are seen in the TEM image of the microcomposite. From these results, one possible mechanism to explain how the peak HRR of the clay nanocomposite is lower than that of neat resin, is the formation of a carbonaceous residue with high thermal stability that acts as a protective barrier by reducing the heat and mass transfer between the flame and the polymer and the progressive increase of the barrier effect induced by reassembly of the clay layers.…”
Section: Flammabilitymentioning
confidence: 99%